Treatment of Venous Thromboembolism in Special Populations with Direct Oral Anticoagulants - Bavalia, Roisin; Middeldorp, Saskia; Weisser, Gerhard; Espinola-Klein, Christine (Thrombosis and Haemostasis, 2020)
As a result of the successful completion of their respective phase III studies compared with vitamin K antagonists (VKAs), four direct oral anticoagulants (DOACs) have been approved for the treatment and secondary prevention of venous thromboembolism (VTE). These DOACs—apixaban, dabigatran, edoxaban, and rivaroxaban—have subsequently seen a steady uptake among clinicians since their approval. Despite the suitability of DOACs for a broad range of patients, they are not appropriate in certain situations, whereas in others they require additional considerations such as dose reductions. Subanalyses of phase III trials and studies on specific VTE patient populations have been conducted to evaluate the safety and efficacy of the DOACs in a broad range of settings, such as patients with renal impairment, patients with cancer, patients of childbearing potential, patients with multiple comorbidities and pediatric patients. Furthermore, many recent guidance documents from important hematological societies and other specialists have incorporated several of these developments. These documents also identify the patients for whom DOACs are not suitable and where traditional anticoagulation options such as heparins or VKAs should be considered instead. This review provides an overview of key VTE patient subgroups, the clinical evidence supporting the use of anticoagulation in these patients, and a discussion of the most appropriate approaches to their management, including considerations such as dosing, acute and extended treatment durations, and DOAC selection.
Keywords: comorbidities; direct oral anticoagulants; special populations; venous thromboembolism